2008
DOI: 10.4067/s0717-95022008000100022
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Histomorphology and Histochemistry of Ampulla of Vas Deferens of Gaddi Goat and Gaddi Sheep

Abstract: SUMMARY:The present study was conducted to record the seasonal variation in the histomorphology and the histochemistry of the ampulla of vas deferens of Gaddi goat and Gaddi sheep, one of the most important breeds of Himachal Pradesh, India. The study was conducted over a period of year during different seasons viz. spring (March -May), summer (June -August), autumn (SeptemberNovember), winter (December-February).Six adult animals of each species were utilized to study histomorphology and histochemical in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Thus it has role in regulating reproductive ability of animals (Suri et al 2012). The secretions of glands provide the substrate for conveying the sperm to the female genital tract and ensuring final maturation (Pathak et al2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it has role in regulating reproductive ability of animals (Suri et al 2012). The secretions of glands provide the substrate for conveying the sperm to the female genital tract and ensuring final maturation (Pathak et al2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies have been reported on the enzyme histochemistry of accessory sex glands during different seasons in Gaddi Goat and Gaddi Sheep (Suri et al 2012) and donkey (Elhamd et al 2013), age related variation in buffalo (Sudhakar, 1982, Chopra, 1998, Anurag, 2000, Bangladeshi bull (Rahman et al 2010), ram (Roy et al1987, Selvinjose et al2009, and boar (Nagasailaja et al 2016). But the histoenzymic variation in buffalo accessory sex glands during different seasons sare still lacking, so the present investigation was carried out to study the distribution pattern of phosphatases, oxidoreductases and estrases with its functional activity in summer and winter seasons.…”
Section: Introductionmentioning
confidence: 99%